Coexistence of Trisomy 13 and SRY (−) XX Ovotesticular Disorder of Sex Development. (2nd November 2017) - Ürel Demir, Gizem; Doğan, Özlem Akgün; Şimşek Kiper, Pelin Özlem; Utine, Gülen Eda; Boduroğlu, Koray; Gucer, Safak; Alikaşifoğlu, Mehmet
ABSTRACT: Introduction: Ovotesticular disorder of sex development (OT-DSD) is a rare disorder of sexual differentiation characterized by the presence of both testicular and ovarian tissue in an individual and the majority of cases have been reported with 46, XX karyotype. In 46, XX cases, testicular differentiation may occur due to the translocation of SRY to the X chromosome or to an autosome. Case report: Herein, we present a female newborn with a combination of trisomy 13 and SRY (-) XX OT-DSD. Conclusion: Trisomy 13 is a relatively common and well-known chromosomal disorder in which disorders of sexual differentiation are not frequent. In the absence of SRY, overexpression of pro-testis genes, or decreased expression of pro-ovarian/anti-testis genes have been suggested as underlying mechanisms of testicular formation. The findings in this patient were suggestive of an underlying genomic disorder associated with FGF9 and/or SPRY2.